Kritik Sosial dalam Novel Belenggu Karya Armijn Pane - Sari, Maya; Zulfadhli, Zulfadhli (Lembaga Yasin AlSys, 2026)
This study aimed to describe the forms of social criticism in the novel Belenggu by Armijn Pane, encompassing criticism of gender injustice, family disorganization, and cultural shift. It employed a descriptive qualitative approach in literary studies, with data consisting of linguistic units (words, phrases, clauses, and sentences) drawn from character dialogues and the narrator’s discourse that represent social criticism in the text. The researcher served as the main instrument through intensive reading, note-taking, and data classification. Data were collected through close reading, systematic note-taking, and the inventory of relevant quotations, while data validity was ensured using theoretical triangulation. Data analysis was conducted by grouping the findings according to the forms of social criticism and then interpreting them descriptively in line with the social context underlying the text. The results showed that the novel Belenggu contains criticism of a patriarchal structure that restricts women’s roles, fractures in family relationships caused by weak emotional communication, and the dominance of Western culture that displaces local cultural values. Overall, the novel reflects the dynamics of social change in Indonesian society during a transitional period toward modernity through its representation of gender conflict, family crisis, and cultural transformation.